Public Health in Developing Countries - Challenges and Opportunities 2020
DOI: 10.5772/intechopen.89602
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in School Children in India

Abstract: The global prevalence of obesity has doubled from 1990 to 2015. Worryingly, the increase is more in children than in adults. In just three decades, the number of school-going children and adolescents with obesity has increased by 10-fold, and the International Association for the Study of Obesity (IASO) and International Obesity Task Force (IOTF) reckon that 200 million school children worldwide are either overweight or obese. The prevalence of obesity among 5-to 19-year-old Indian children, ranged between 3.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 84 publications
2
6
0
Order By: Relevance
“…Studies in developed countries reported that only 33% of adolescents fulfil a recommended goal of at least 60 min of physical activity per day ( 32 ). Nearly half of the children in our study did not exercise any sport, which is similar to the situation among schoolchildren in other parts of Serbia ( 33 ) and in India ( 34 ). Sedentary behavior can negatively affect mental and cognitive health in children and adolescents with obesity ( 35 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Studies in developed countries reported that only 33% of adolescents fulfil a recommended goal of at least 60 min of physical activity per day ( 32 ). Nearly half of the children in our study did not exercise any sport, which is similar to the situation among schoolchildren in other parts of Serbia ( 33 ) and in India ( 34 ). Sedentary behavior can negatively affect mental and cognitive health in children and adolescents with obesity ( 35 ).…”
Section: Discussionsupporting
confidence: 85%
“…There is compelling evidence showing that sitting by personal computer too much may impair physical, mental and cognitive health in children and adolescents ( 34 , 45 ). In relation to our own contribution to the field, we found a statistically significant association between daily Internet use (sedentary lifestyle) and obesity, hyperactivity-inattention, emotional symptoms, conduct problems and social maladjustment.…”
Section: Discussionmentioning
confidence: 99%
“…1 The prevalence of obesity among 5-to 19-year-old Indian children, ranged between 3.6 and 11.7% and It is predicted that by 2025 there will be 17 million obese children in India. 2 The prevalence of hypertension, type 2 diabetes, dyslipidemia and non-alcoholic fatty liver disease in children is also increasing with increasing obesity. Risk of obesity and lack of outdoor exposure in childhood also touches the field of Otorhinolaryngology.…”
Section: Legal Disclaimermentioning
confidence: 99%
“…About 10% of children aged between 5-17 years have come under the category of obese or overweight. 4 Gupta et al conducted a systematic review and reported that in India, children between 5-19 years have a prevalence of overweight ranging between 6.1% and 25.2%, and the prevalence of obesity ranged between 3.6% and 11.7%. 5 Among schoolaged children, junk food, is a major contributor to increasing overweight from 9.7% -13.9% between 2001-2010.…”
Section: Introductionmentioning
confidence: 99%